Do firms adapt to climate change? Evidence from establishment-level data - LI, Frank Weikai (Institutional Knowledge at Singapore Management University, 2020)
This paper examines firms’ adaptation to long-term changes in climatic conditions. Using detailed information of establishments owned by U.S. public firms from 1990 to 2012, we show that higher abnormal temperatures over the previous five years in a county lead to a significant reduction in local employment and the number of establishments. Further tests suggest that the decline in employment and establishments is largely due to a decline in local consumer demand rather than lower labor productivity. We also find that firms more likely take adaptive actions when their managers are more likely to believe in, or are concerned about, climate change. Overall, we provide large-sample evidence on firm adaptation to climate change.